INVESTIGATING FOREIGN LANGUAGE ENJOYMENT AMONG NON-ENGLISH MAJOR MALAYSIAN UNDERGRADUATES - Ahmad, Adi Afzal (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Emotion has been shown to play a significant role in language learning. For decades, researchers have been carrying out studies on negative emotion such as foreign language anxiety, its influence on second language learners and the learning process. Not many studies have been conducted on positive emotion such as foreign language enjoyment. This study, therefore, aims to fill in the gap by exploring the role of foreign language enjoyment among non-English major Malaysian undergraduates. The main objective of the study was to identify the level of foreign language enjoyment among the undergraduates. Subsequent objectives included examining the role of gender and identifying the factors that contribute to foreign language enjoyment. A total of 338 university students took part in the study by completing the research questionnaire. Data analysis indicated a high level of foreign language enjoyment among the students. In addition, gender was found to have a significant influence on the level of foreign language enjoyment. Finally, some of the key contributing factors to foreign language enjoyment, as indicated by the students, included perceived benefits, supportive peers and instructors, and positive classroom atmosphere.